Robinson Reflections Part 3: Paper Chase — The Story of Mary Robinson's Arranged Marriage. (September 2013) - Gamble, Bob
Abstract : 'Paper Chase' is the third of three complementary articles collected as 'Robinson Reflections'.* It further examines the reactions of the Robinson and Brontë families in the period following Branwell's dismissal from Thorp Green Hall in July 1845. By linking the papermaking industry in Airedale to that in Derbyshire's Derwent valley, the work provides evidence that the arrival in Keighley in late 1848 of the newly-married Mary Robinson/Clapham (daughter of Lydia Robinson) was not an accident of fate, but a deliberately planned arrangement driven by the business and political interests of her uncle, William Evans MP of Allestree Hall.